2006
DOI: 10.1007/s00270-005-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Splenic Cyst Treated with Percutaneous Sclerosis Using Alcohol

Abstract: We report a case of successful percutaneous treatment of a congenital splenic cyst using alcohol as the sclerosing agent. A 14-year-old female adolescent presented with a nonsymptomatic cystic mass located in the spleen that was believed to be congenital. After ultrasonography, a drainage catheter was placed in the cavity. About 250 ml of serous liquid was extracted and sent for microbiologic and pathologic studies to rule out an infectious or malignant origin. Immediately afterwards, complete drainage and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…(1) Computed tomography is more sensitive than ultrasound in identifying septa and calcifications. (5) Cystic lesions on CT are spherical, well-defined, with attenuation equivalent to the water, with a thin or imperceptible capsule. (6) Splenic cysts may contain areas with a high density due to bleeding, increased protein content, or purulent material into the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Computed tomography is more sensitive than ultrasound in identifying septa and calcifications. (5) Cystic lesions on CT are spherical, well-defined, with attenuation equivalent to the water, with a thin or imperceptible capsule. (6) Splenic cysts may contain areas with a high density due to bleeding, increased protein content, or purulent material into the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography is more sensitive than ultrasound in the identification of septa (more common in true cysts) or calcifications (more common in false cysts) 44 . In MRI the cyst is hypointense on T1-weighted images, with strongly hyperintense images on T2, with signal intensity equal to water without reinforcement after contrast injection.…”
Section: Imaging Tests Imaging Tests Imaging Tests Imaging Testsmentioning
confidence: 99%
“…Due to the increased risk of complications, splenic cysts with a diameter greater than 4-5 cm should be surgically treated 10,12 , as conservative treatment options, such as percutaneous aspiration or sclerosis, do not result in good long term control 11 . Some studies have shown that splenic cyst sclerosis with alcohol was successful for small lesions (up to 11 mm) but not for large ones 44 . Treatment options are: partial splenectomy, total cystectomy, cyst marsupialization or decapsulation, with access either by laparotomy or laparoscopy 11,12,43 .…”
Section: Imaging Tests Imaging Tests Imaging Tests Imaging Testsmentioning
confidence: 99%
“…Because of the immunologic role of the spleen, new surgical approaches, such as laparoscopic surgery, partial splenectomy, decapsulation and unroofing, have been proposed [ 5 ]. Recently, conservative treatment using percutaneous aspiration of the cyst contents with or without instillation of sclerosing agents has been generally accepted [ 6 ]. High success rates of alcoholic sclerotherapy in patients with renal and hepatic cysts have been reported [ 7 8 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…High success rates of alcoholic sclerotherapy in patients with renal and hepatic cysts have been reported [ 7 8 9 ]. However, there are contradictory reports regarding congenital splenic cysts treated with percutaneous sclerosis using alcohol [ 6 10 ]. The optimal treatment of post-traumatic splenic pseudocysts is not well defined.…”
Section: Introductionmentioning
confidence: 99%